The Learning Delivery Modalities in Catanduanes State University - Antonio, Julius S. (Future Science / FSH-PH Publications, 2021)
The suspension of conduct of face-to-face learning has shifted the Catanduanes State University (CatSU) to adapt flexible blended learning in delivering instruction and learning experiences to its students. As directed by the Commission on Higher Education, universities and colleges in the Philippines should adapt flexible blended learning. With limited training on blended learning, the CatSU faculty members are prone to some limitations and drawbacks while implementing the adapted Learning Delivery Modalities (LDMs). An investigation on the implementation of LDMs in CatSU revealed that faculty members used blended learning that is a combination of online synchronous or asynchronous classes to offline modular distance learning. The platform used by the faculty members in conducting synchronous classes were Zoom and Google Meet. On the other hand, the platform used in conducting asynchronous sessions was Google Classroom. While the adapted flexible blended learning of CatSU faculty members include online learning, a few faculty members reported that they had trouble in contacting their students since either the students don’t own mobile phones, or they don’t have phone signals at home. Some faculty members considered having not provided with internet service at school as a minor problem. Possible solutions for the different problems encountered by the faculty members have been recommended in this study.